2021
DOI: 10.1186/s13046-021-01841-w
|View full text |Cite
|
Sign up to set email alerts
|

Intrabodies targeting human papillomavirus 16 E6 and E7 oncoproteins for therapy of established HPV-associated tumors

Abstract: Background The oncogenic activity of the high risk human papillomavirus type 16 (HPV16) is fully dependent on the E6 and E7 viral oncoproteins produced during viral infection. The oncoproteins interfere with cellular homeostasis by promoting proliferation, inhibiting apoptosis and blocking epithelial differentiation, driving the infected cells towards neoplastic progression. The causal relationship between expression of E6/E7 and cellular transformation allows inhibiting the oncogenic process b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…The result was confirmed using two different HPV16-positive tumour cells, namely C3 and TC-1 cells, and also by employing higher amounts of TC-1 cells to mimic tumours that are more aggressive. Through histology and immunohistochemistry, we showed that the antitumour activity is based on the induction of tumour cell death by apoptosis [72].…”
Section: Scfvs and Mabsmentioning
confidence: 99%
See 3 more Smart Citations
“…The result was confirmed using two different HPV16-positive tumour cells, namely C3 and TC-1 cells, and also by employing higher amounts of TC-1 cells to mimic tumours that are more aggressive. Through histology and immunohistochemistry, we showed that the antitumour activity is based on the induction of tumour cell death by apoptosis [72].…”
Section: Scfvs and Mabsmentioning
confidence: 99%
“…We then investigated the I7nuc antitumour activity in mouse models for HPV tumours based on the injection of HPV16-positive tumour cells in C57BL6 mice. The scFv capability to either prevent cancer development from scFv-expressing tumour cells, or to hinder cancer progression by delivery to already established tumours, was evaluated [71,72] (Figure 4). We observed a clear impairment of tumour growth in all mice injected with TC-1 tumour cells expressing I7nuc by retroviral transduction before inoculation into mice, with 60% of them completely protected from tumour onset for the 4 months of observation time [71].…”
Section: Scfvs and Mabsmentioning
confidence: 99%
See 2 more Smart Citations
“…A scFv intrabody targeting VEGFR2/KDR was selected from an immune phage display library of mice [ 63 ]. Recently, intrabodies targeting human papillomavirus 16 E6 and E7 oncoproteins for the treatment of established HPV-associated tumors were generated from a synthetic human antibody phage display library [ 64 ]. One scFv against 16 E7 was targeted to the ER and interferes with the binding of E7 to retinoblastoma tumor suppressor (pRb).…”
Section: Intrabodies Against Oncogenic Cell Surface Receptorsmentioning
confidence: 99%